The motivation for physical activity is a predictor of VO2peak and is a useful parameter when determining the need for cardiac rehabilitation in an elderly cardiac population - Mikkelsen, Nicolai; Dall, Christian Have; Frederiksen, Marianne; Holdgaard, Annette; Rasmusen, Hanne; Prescott, Eva (PLOS ONE, 2022)
Background Exercise-based cardiac rehabilitation (CR) is an essential contributor to a successful recovery for elderly cardiac patients. The motivation for physical activity is a psychological parameter seldom described in secondary prevention, and it is plausible that motivation contributes to the differential effect of CR. Purpose To investigate if motivation, measured using the behavioural regulation in an exercise questionnaire (BREQ-2), predicts VO2peak in elderly cardiac patients before and after CR. Methods A prospective cohort study of elderly ischemic cardiac patients and patients with valvular disease participating in cardiac rehabilitation was used. Motivation was measured using BREQ-2, which measures five constructs of motivation and a summed score—the relative autonomy index (RAI). VO2peak was measured before and after CR using a cardiopulmonary exercise test (CPET). Results Two hundred and three patients performed the baseline tests and initiated CR. One hundred and eighty-two completed CR and comprised the follow-up group. The mean VO2peak was 18 ml/kg/min (SD±5.1). VO2peak increased significantly with increasing motivation, 1.02 (.41–1.62) ml/kg/min pr. SD. Mean improvement from CR was 2.3 ml/kg/min (SD±4.3), the equivalent of a 12% increase. A change in VO2peak after CR was likewise positively associated with increased motivation, .74 (.31–1.17) pr. SD. Conclusion The level of motivation predicts VO2peak before CR, and is also able to predict changes in VO2peak following CR. Motivation measured with the BREQ-2 questionnaire can be applied as a screening tool for elderly cardiac patients before they initiate CR to identify patients with need of specific attention.